Investment Criteria, Productivity and Economic Development: Comment - Moes, John (Quarterly Journal of Economics, 1957)
Journal Article Investment Criteria, Productivity and Economic Development: Comment Get access John Moes John Moes University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 71, Issue 1, February 1957, Pages 161–164, https://doi.org/10.2307/1882302 Published: 01 February 1957